An infant with intradural extramedullary synovial sarcoma: the youngest case in the literature - Yalçın, Koray; Tüysüz, Gülen; Kazan, Saim; Gürer, Elif İnanç and Karaali, Kamil and Küpesiz, Alphan and Güler, Elif (The Turkish Journal of Pediatrics, 2019)
Spinal cord involvement of synovial sarcoma is extremely rare. So far only two cases have been reported. Herein we describe the youngest case in the literature. She is 14-month-old and first presented with difficulty in walking ongoing for a week. Imagining showed a spinal cord mass at C5-T3 levels. The patient had gone under Decompressive surgery and histopathologic examination of the specimen revealed the presence of synovial sarcoma. Although the tumor regressed after chemotherapy, she was lost due to viral pneumonia. Synovial sarcoma should be kept in mind while evaluating spinal tumors even in infantile group.